2015
DOI: 10.1089/jop.2014.0151
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-2 Expression During Retinal Vascular Development and Neovascularization

Abstract: Purpose: To determine thrombospondin-2 (TSP2) expression and its impact on postnatal retinal vascular development and retinal neovascularization. Methods: The TSP2-deficient (TSP2 -/ -) mice and a line of TSP2 reporter mice were used to assess the expression of TSP2 during postnatal retinal vascular development and neovascularization. The postnatal retinal vascularization was evaluated using immunostaining of wholemount retinas prepared at different postnatal days by collagen IV staining and/or TSP2 promoter d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
1
14
2
Order By: Relevance
“…This was further confirmed by using wholemount staining and Western blot analysis of TSP2-GFP reporter mice. However, TSP2 protein levels (GFP-reporter) were undetectable at P42 [72]. This is consistent with limited expression of TSP2 protein observed in adult retina.…”
Section: Amd and Endogenous Inhibitors Of Angiogensissupporting
confidence: 68%
See 2 more Smart Citations
“…This was further confirmed by using wholemount staining and Western blot analysis of TSP2-GFP reporter mice. However, TSP2 protein levels (GFP-reporter) were undetectable at P42 [72]. This is consistent with limited expression of TSP2 protein observed in adult retina.…”
Section: Amd and Endogenous Inhibitors Of Angiogensissupporting
confidence: 68%
“…We showed that the primary retinal vasculature develops at a faster rate in Thbs2 −/− mice with a minimal impact on the rate of vascular cell proliferation and apoptosis. Thbs2 -deficiency also minimally affected the degree of retinal and choroidal neovascularization [72]. However, TSP2 level was significantly up-regulated in P17 mice subjected to OIR.…”
Section: Amd and Endogenous Inhibitors Of Angiogensismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] In the retinal vasculature, pericytes are the major source of TSP2 expression, and its expression is further enhanced under oxidative stress. [ 27 28 ] However, the cell autonomous role of TSP2 expression in retinal vascular cells and the characteristics of TSP2-null vascular cells compared with wild type cells have yet to be studied, as we have reported for TSP1. However, we recently demonstrated that the germline deletion of TSP2 minimally affects the postnatal retinal vascular development and neovascularization.…”
Section: Thrombospondin-1 Expression In Retinal Vascular Cellsmentioning
confidence: 89%
“…However, we recently demonstrated that the germline deletion of TSP2 minimally affects the postnatal retinal vascular development and neovascularization. [ 28 ]…”
Section: Thrombospondin-1 Expression In Retinal Vascular Cellsmentioning
confidence: 99%